PENERAPAN SAPTA PESONA PADA OBJEK WISATA DANAU BANDAR KHAYANGAN KOTA PEKANBARU - Rahmadani, Rahayu; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to analyze the implementation of the Sapta Pesona concept in the management of the Bandar Khayangan Lake Lembah Sari tourist destination in Pekanbaru City and evaluate its impact on tourist appeal. The research employs a qualitative method with data collection through observation, interviews, and documentation. The study focuses on the application and principles of Sapta Pesona.The results show that Bandar Khayangan Lake has significant potential as a leading tourist destination due to its natural beauty, adequate supporting facilities, and easy accessibility. However, challenges such as inadequate facility maintenance, cleanliness management, and supervision remain key obstacles. Strategic measures undertaken include reforestation, facility improvement, visitor education, and collaboration with local communities. The implementation of Sapta Pesona has proven effective in creating a safe, comfortable, and memorable tourism experience, ultimately increasing tourist interest. This study concludes that Sapta Pesona-based management can be an effective strategy to support sustainable tourism development but requires synergy between the government, managers, and local communities to achieve optimal results. Keywords: Implementation, Sapta Pesona, Bandar Khayangan Lake